ESTETIKA TAMAN KARESANSUI DARI PANDANGAN ZEN BUDDHISME - vivin vistya elfina (Jurnal Pustaka Nusantara dan Budaya, 2013)
Karesansui garden is a dry garden which spread almost all over Japan. This garden doesn’t use water but describes the water based on topography. Besides karesansui garden is one of the Japanese garden that influenced by Zen Buddhism. Generally, Japanese aesthetics is not much different with aesthetics value that exist in Zen Buddhism. In writing this paper the author uses library research and descriptive analyzes were done by describing the data that author got from any references and then analyze it. Moreover, the author use a religious theory, especially those leads to Zen Buddhism thought, wabi-sabi aesthetic theory and theory of semiotics. The purpose of this research is to know about moral values of Zen Buddhism in Japan and the moral values of Zen Buddhism on Karesansui garden’s aesthetics.  The result of this research is there are five Zen Buddhism aesthetic values in Karesansui garden. They are the value of asymmetry, the value of simplicity, the value of naturalness, the value of the essence of time, and the value of dept of meaning.